Metaphor and myth as elements of artistic-language - V. I. Panchenko (Ukrainian Cultural Studies, 2019)
The article is devoted to analysis of the artistic culture structure. Artistic culture has developed its main structural elements that provide a certain logic of artistic thinking and artistic creativity and which are the basis of any work of art. These structural elements – rhythm, intonation, metaphor, myth (as a way of action organizing, as a prototype of composition), archetypes and archetypal symbols – are the main artistic means that "work" in all types of art, while defining the specifics (due to their dominance) of the each one of them.